China's Semiconductor Market Prospects in the Next Several Years - Zong, Xuanyu (Transactions on Economics, Business and Management Research, 2024)
Semiconductors are the core of the modern electronics industry and are crucial for economic growth, national security, technological innovation, and global competitiveness, which can promote technological innovation and economic development. Nowadays, the market scale of semiconductors expends a lot in China every year, since it is the critical component for everything from consumer electronics to advanced AI. The use of semiconductors because they are the essential materials that enable the operation of modern electronics. Semiconductors have unique properties that allow them to act as either conductors or insulators depending on the conditions, such as the application of voltage or light. This versatility makes them ideal for building electronic components like transistors, diodes, and integrated circuits (ICs), which are the building blocks of all electronic devices. Without question, the use of semiconductors is increasing after it shows up in everyone's view. Therefore, this research introduces the requirement for semiconductors in the overall market and the prospects in the next ten years.